An assessment of storage practices of essential medicines in primary health centers of Gadag taluk, Karnataka - Tejesh, S.; S. J., Nagaveni (International Journal Of Community Medicine And Public Health, 2023)
Background: The efficacy and safety of medications may be impacted by the potency loss that occurs during storage. Pharmaceuticals need to be stored under controlled conditions and transportation situations to make sure its quality isn't harmed. A crucial component of the overall drug control system is storage. Wherever pharmaceuticals and supplies are kept on the property, sufficient environmental control must be maintained, including the right temperature, light, and humidity levels, as well as sanitary, ventilation, and segregation requirements. Methods: A cross sectional study was done to assess the Storage conditions of medicines in pharmacies of primary health centers of Gadag Taluk. Storage facilities was assessed using observational checklist. Sampling design was universal sample all 15 primary health centers (PHCs) as per health management information system (HMIS) data was assessed for Storage conditions of essential medicine in primary health centre. Results: Results indicate that storage conditions for essential medicines are: 80% of pharmacies have a dedicated warehouse or storage space for drugs; 100% have a method to control temperature; 93.33% have cold storage facilities; 100% use racks; only 33.3% have drugs arranged with identification labels; manufacturing dates and expiration dates are clearly visible; and medicines are stored in a systemic way. Conclusions: In summary, the primary health centre's pharmacies are generally storing medications correctly, but there is room for improvement. Labelling drugs, managing expired drugs, and training staff can help improve storage and drug supply. These measures can ensure better medication storage conditions.